Pengaruh Aktivitas Masyarakat di Sekitar Pemukiman Lahan Basah terhadap Pencemaran Air - Fariha, Aisyatu Najiyatil; Sunarsih, Elvi; Amelia, Meisya; Aditya, Muhammad Pandu; Auliya, Nur Zahrotul; Fransisca , Yolanda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Wetlands are areas of swamp, brackish, peatland, and waters, permanent or temporary, with stagnant or flowing, fresh, brackish, or salt water, including areas of marine waters the depth of which at low tide does not exceed six meters. A wetland is an area where water has a permanent or seasonal presence. This study article uses research methods literature on a qualitative approach to obtain descriptive data by collecting data through literature review. As the human population increases, more and more of people choose to live outside the city, according to the analysis results, such as residential areas near wetlands. The presence of water is integral to the daily activities of communities living around wetlands. People who regularly engage in daily activities like bathing, cooking, washing, and using floating toilets may contribute to water pollution. This is due to the lack of knowledge and public awareness, leading to a negative perception of environmental cleanliness. These social activities eventually impact environmental quality, leading to water pollution.